Collection of simulated XRD powder patterns for zeolites. - Treacy, M. M. J. (Michael M. J.) (Elsevier, 2001)
Collection of Simulated XRD Powder Patterns for Zeolites serves as a source of reference patterns for pure zeolite phases. The data will be helpful in establishing the structural purity of experimental phases and in indexing their diffraction patterns. The information will also aid in the determination of changes in the lattice parameters with changing composition, assessing preferred orientation effects, background evaluation, and line broadening. Also included are diffraction patterns of several common dense silicate phases to facilitate their detection in mixed phase synthesis.